2016
DOI: 10.1007/s00198-016-3560-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of twelve-month physical exercise program on patients with osteoporotic vertebral fractures: a randomized, controlled trial

Abstract: This is the first 12 month-randomized clinical trial of exercise in osteoporotic women with a vertebral fracture that demonstrates improvement of three key outcome measures: quality of life, functional mobility, and balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 26 publications
1
46
2
1
Order By: Relevance
“…Wang and colleagues also reported a significant between‐group difference in favor of the intervention for self‐reported physical function using the ODI after 6 and 12 months. Finally, a recent study reported that the exercise intervention led to a significant improvement in some subscales of the QUALLEFO‐41 questionnaire, including jobs around the house subscale and mobility subscale, but no change in activities of daily living subscale . In summary, there is some evidence of small benefit in longer term follow‐up when it comes to self‐reported function/disability.…”
Section: The Efficacy and Safety Of Vertebral Augmentation: Task Forcmentioning
confidence: 98%
“…Wang and colleagues also reported a significant between‐group difference in favor of the intervention for self‐reported physical function using the ODI after 6 and 12 months. Finally, a recent study reported that the exercise intervention led to a significant improvement in some subscales of the QUALLEFO‐41 questionnaire, including jobs around the house subscale and mobility subscale, but no change in activities of daily living subscale . In summary, there is some evidence of small benefit in longer term follow‐up when it comes to self‐reported function/disability.…”
Section: The Efficacy and Safety Of Vertebral Augmentation: Task Forcmentioning
confidence: 98%
“…Previous studies have reported the benefits of muscle strength exercise in the clinical management of patients with osteoporotic vertebral fractures. [14][15][16] We tried to start physical therapy as soon as possible to prevent disuse weakness.…”
Section: Discussionmentioning
confidence: 99%
“…BSE will be conducted with a computerized posturographic system for diagnosing balance and movement skills (Balance Master System NeuroCom; Natus Medical Inc., Pleasanton, CA) designed to objectively quantify balance and postural function of different origins, as described previously. [ 13 ] Briefly, subjects will be prepared by being introduced to the supported standing position with the objective of looking for a symmetrical load on their legs. In the introductory session, dynamic exercises for small- and medium-sized muscle groups and lower extremity joints will be performed.…”
Section: Methodsmentioning
confidence: 99%